Hemodynamic Profile of Target-Controlled Spinal Anesthesia Compared With 2 Target-Controlled General Anesthesia Techniques in Elderly Patients With Cardiac Comorbidities. Issue 4 (1st July 2012) - Biboulet, Philippe; Jourdan, Alexandre; Van Haevre, Vera; Morau, Didier; Bernard, Nathalie; Bringuier, Sophie; Capdevila, Xavier
Abstract : Background and Objectives: The impact of anesthesia techniques in patients experiencing hip fracture is controversial. This study compares the effects on blood pressure of 3 anesthesia techniques that are considered safe for the elderly. Methods: Forty-five patients older than 75 years, with American Society of Anesthesiologists physical status III or IV, with cardiac comorbidities, and undergoing surgery for hip fracture, were randomized to receive continuous spinal anesthesia (CSA), propofol target-controlled infusion (TCI), or sevoflurane (SEVO). In CSA patients, a T10 metameric level target was achieved by titration of 2.5 mg of bupivacaine boluses. In patients on TCI and SEVO, a bispectral value target of around 50 guided the concentration of propofol or sevoflurane. Analgesia in the TCI and SEVO groups was provided with remifentanil. Hypotension was defined as a 30% decrease in mean arterial pressure and was treated with an intravenous bolus of ephedrine. Results: The number of hypotension episodes was lower in the CSA group: 0 (range, 0–6) versus 11.5 (range, 1–25) in the TCI group and 10 (range, 1–23) in the SEVO group ( P < 0.001). Both TCI and SEVO patients needed more ephedrine compared with CSA patients (30.5 [15.5], 26 [23], and 1.5 [2.5] mg, respectively, P < 0.001). The maximal decrease in mean arterial pressure was lower in the CSA group (26% [17%]) compared with that in the TCI group (47% [8%]) and the SEVO group (46% [12%]; P < 0.001). Conclusions: In elderly patients, spinal anesthesia using titrated doses of bupivacaine provided better blood pressure stability than propofol or sevoflurane anesthesia.